Heterologous Production of an Energy-Conserving Carbon Monoxide Dehydrogenase Complex in the Hyperthermophile Pyrococcus furiosus - Schut, Gerrit J.; Lipscomb, Gina L.; Nguyen, Diep M. N.; Kelly, Robert M.; Adams, Michael W. W. (Frontiers in Microbiology, 2016)
Carbon monoxide (CO) is an important intermediate in anaerobic carbon fixation pathways in acetogenesis and methanogenesis. In addition, some anaerobes can utilize CO as an energy source. In the hyperthermophilic archaeon Thermococcus onnurineus, which grows optimally at 80°C, CO oxidation and energy conservation is accomplished by a respiratory complex encoded by a 16-gene cluster containing a carbon monoxide dehydrogenase, a membrane-bound [NiFe]-hydrogenase and a Na+/H+ antiporter module. This complex oxidizes CO, evolves CO2 and H2, and generates a Na+ motive force that is used to conserve energy by a Na+-dependent ATP synthase. Herein we used a bacterial artificial chromosome to insert the 13.2 kb gene cluster encoding the CO-oxidizing respiratory complex of T. onnurineus into the genome of the heterotrophic archaeon, Pyrococcus furiosus, which grows optimally at 100°C. P. furiosus is normally unable to utilize CO, however, the recombinant strain readily oxidized CO and generated H2 at 80°C. Moreover, CO also served as an energy source and allowed the P. furiosus strain to grow with a limiting concentration of sugar or with peptides as the carbon source. Moreover, CO oxidation by P. furiosus was also coupled to the re-utilization, presumably for biosynthesis, of acetate generated by fermentation. The functional transfer of CO utilization between Thermococcus and Pyrococcus species demonstrated herein is representative of the horizontal gene transfer of an environmentally-relevant metabolic capability. The transfer of CO utilizing, hydrogen-producing genetic modules also has applications for biohydrogen production and a CO-based industrial platform for various thermophilic organisms.